Modelling a hybrid system pv/wind grid connected with static synchronous compensator (STATCOM) - Abusalim, Ghazi W. G. (2020)
Whenever s photo voltaic and wind power production are used together, the reliability xof the power grid is enhanced. But this combined hybrid system needs controlling and Compensation, to overcome this problem, we use Static x Synchronous Compensator (STATCOM) to stabilize the power supply at the grid side after many disturbances via Voltage Sag, load changes, Distortion etc. This thesis contain modelling of Photovoltaic renewable energy system to produces maximum 5 KW/h. Moreover, the study contains modelling of wind energy system to produces 1.5 KW/h. reducing the effect of the intermittent nature of renewable sources on the electricity generation is a challenging task. The maximum power is 6.5 KW/h obtained using hybrid system. Thiss thesis investigates the use of as Static Synchronous Compensator (STATCOM) alongs with wind energys and solar for sthe purposes of stabilizings the grid voltages using MATLAB/Simulink.